A Participatory Approach to the Sustainable Development of an Historic Landscape; Management Plan Proposal for Hisar District, Bursa/Turkey. (2nd January 2021) - Çahantimur, Arzu Ispalar; Öztürk, Rengin Beceren
ABSTRACT: Hisar District is located within the borders of Osmangazi County. Hisar has a rich historical and cultural heritage and is a valuable historic landscape which carries not only the physical and spatial traces of this heritage but also preserves social and cultural features. With these features, Hisar District should be conserved for a sustainable future. Bursa Metropolitan Municipality considered the Hisar (Citadel) District as an Ottoman and World Heritage site and a research team from Bursa Uludag University has been given the task of preparing a management plan as a project in order to achieve conservation of the site with a sustainable approach. Led by the author of this paper, Dr Çahantimur, Bursa Uludag University Project Team prepared the plan with a place-specific and participatory approach. This study presents both the significance of Hisar heritage site and the participatory process of the site management plan. It also presents a critical review of the actions undertaken by the municipality since then.